MiR-450a-5p Inhibits Gastric Cancer Cell Proliferation, Migration, and Invasion and Promotes Apoptosis via Targeting CREB1 and Inhibiting AKT/GSK-3β Signaling Pathway - Zhao, Ya-Jun; Zhang, Jun; Wang, Yong-Cang; Wang, Liang; He, Xin-Yang (Frontiers in Oncology, 2021)
Gastric cancer seriously affects human health and research on gastric cancer is attracting more and more attentions. In recent years, molecular targets have become the research focus. Accumulating evidence indicates that miR-450a-5p plays a critical role in cancer progression. However, the biological role of miR-450a-5p in gastric carcinogenesis remains largely unknown. In this study, we explore the effects and mechanisms of miR-450a-5p on the development and progression of gastric cancer. We used gain-of-function approaches to investigate the role of miR-450a-5p on gastric cancer cell proliferation, migration, invasion, and apoptosis using biological and molecular techniques including real-time quantitative PCR (RT-qPCR), CCK-8, colony formation, flow cytometry, Western blot, wound healing, transwell chamber, dual luciferase reporter and tumor xenograft mouse model. We found that gastric cancer cells have low expression of miR-450a-5p and overexpression of miR-450a-5p inhibited gastric cancer cell proliferation, migration and invasion, and induced apoptosis in vitro. Moreover, we demonstrated that ectopic expression of miR-450a-5p inhibited gastric cancer growth in vivo. At the molecular level, overexpression of miR-450a-5p significantly increased the expression of pro-apoptotic proteins, including Caspase-3, Caspase-9 and Bax, and inhibited the expression of anti-apoptotic protein Bcl-2. Luciferase reporter experiment suggested that Camp Response Element Binding Protein 1 (CREB1) had a negative correlation with miR-450a-5p expression, andknockdown of CREB1 alleviated gastric cancer growth. Furthermore, we also found that miR-450a-5p inhibited the activation of AKT/GSK-3β signaling pathway to inhibit the progression of gastric cancer. Collectively, miR-450a-5p repressed gastric cancer cell proliferation, migration and invasion and induced apoptosis throughtargeting CREB1 by inhibiting AKT/GSK-3β signaling pathway. MiR-450a-5p could be a novel molecular target for the treatment of gastric cancer.